Dissipation measurements using an MSS profiler in summer 2022, during the RV Polarstern PS131 cruise, ATWAICE - Ilker Fer; Simon F Reifenberg (PANGAEA, 2025)
Ocean microstructure profiles were obtained from a MSS (Microstructure Sensor Profiler, Sea&Sun Technology, Germany) profiler between 13 July and 6 August 2022 during the RV Polarstern PS131 cruise, ATWAICE, from ice floes as well as at stations from the ship. The aim of this expedition was to investigate sea ice summer melt processes, with a focus on the contribution of the Atlantic water inflow into the region. In total, 183 files of single casts are submitted, of which 19 were collected from ship and 164 from ice. Please see the detailed log spreadsheet for stations and comments. Throughout the cruise, the instrument functioned well, except the vibration sensor did not work and the fast thermistor channel produced a cut-off at low end, probably for output that exceeded the range of the A/D converter of the probe. In the later part of the cruise episodic data transmission errors were encountered. The dissipation rate was measured using two airfoil shear probes. The dataset has been processed and formatted in accordance with the SCOR Working Group ATOMIX guidelines and recommendations (Lueck et al., 2024; https://doi.org/10.3389/fmars.2024.1334327). One NetCDF (NC) file per instrument extquotesingles native file is provided. Each provided NC file is organized in five hierarchical groups including continuous time series of data converted into physical units, cleaned time series used for spectral analysis, wavenumber spectra, dissipation rate estimates, and 0.1 dbar vertically averaged profiles from the precision conductivity, temperature and auxiliary sensors. The temperature and the practical salinity obtained from the MSS are corrected against the shipboard SBE-911plus CTD system (calibrated against salinity water samples). The grouped NC files are large and may be impractical to download and merge. For users only interested in the dissipation estimates and other time-averaged profiles, we also provide two separate NC files with all dissipation rate (and other related parameters) profiles and 0.1-dbar vertically averaged sensor data, collated into one file each. The collated files are, additionally, manually quality controlled and cleaned, whereas the per-file NC files are screened using automated routines. For more detailed information, please refer to the comments within the data file. The raw (binary, native format), full-resolution data from the microstructure profiler are available from Fer et al. (2023), https://doi.org/10.1594/PANGAEA.956086. The observations on ice floes are complemented by simultaneous ocean current measurements from an ice-mounted Acoustic Doppler Current Profiler, see https://doi.org/10.1594/PANGAEA.978165.